Eastern Pacific Coral Reef Provinces, Coral Community Structure and Composition: An Overview - Glynn, Peter W. (2017)
Advances in our knowledge of eastern tropical Pacific (ETP) coral reef biogeography and ecology during the past two decades are briefly reviewed. Fifteen ETP subregions are recognized, including mainland and island localities from the Gulf of California (Mexico) to Rapa Nui (Easter Island, Chile). Updated species lists reveal a mean increase of 4.2 new species records per locality or an overall increase of 19.2 % in species richness during the past decade. The largest increases occurred in tropical mainland Mexico, and in equatorial Costa Rica and Colombia, due mainly to continuing surveys of these under-studied areas. Newly discovered coral communities are also now known from the southern Nicaraguan coastline. To date 47 zooxanthellate scleractinian species have been recorded in the ETP, of which 33 also occur in the central/south Pacific, and 8 are presumed to be ETP endemics. Usually no more than 20–25 zooxanthellate coral species are present at any given locality, with the principal reef-building genera being Pocillopora, Porites, Pavona, and Gardineroseris. This compares with 62–163 species at four of the nearest central/south Pacific localities. Hydrocorals in the genus Millepora also occur in the ETP and are reviewed in the context of their global distributions. Coral community associates engaged in corallivory, bioerosion, and competition for space are noted for several localities. Reef framework construction in the ETP typically occurs at shallow depths (2–8 m) in sheltered habitats or at greater depths (10–30 m) in more exposed areas such as oceanic island settings with high water column light penetration. Generally, eastern Pacific reefs do not reach sea level with the development of drying reef flats, and instead experience brief periods of exposure during extreme low tides or drops in sea level during La Niña events. High rates of mortality during El Niño disturbances have occurred in many ETP equatorial areas, especially in Panama and the Galápagos Islands during the 1980s and 1990s. Remarkably, however, no loss of resident, zooxanthellate scleractinian species has occurred at these sites, and many ETP coral reefs have demonstrated significant recovery from these disturbances during the past two decades.